Early engagement with the wider patient community in early‐phase clinical trial design: Insights from the CareRing caregiver community in designing the Brainshuttle AD trial. (1st February 2022) - Croney, Ruth; Agnew, David; Vogt, Annamarie; Alcaraz, Fabien; Svoboda, Hanno; Kulic, Luka; Proulx, Léa
Abstract: Background: Caregivers and families of people with Alzheimer's disease (AD) play a crucial role in the decision to participate in a clinical trial, and in supporting participants during the trial process. Early engagement with the wider patient community could enable the design of trials that are less burdensome for participants and caregivers. The CareRing initiative gathered caregiver insights on: participant/caregiver motivations for involvement in early phase clinical trials where no treatment benefit is expected; the role caregivers expect to play when loved ones participate in a trial; and holistic support that could help minimize the impact of trial participation on daily life. Method: Six Roche employees from different geographical regions with varying backgrounds and roles, who are caregivers for a person with AD, participated in two 60‐minute telephone calls. The calls included presentations of the Roche brain shuttle technology and draft protocol for the Phase IB/IIA Brainshuttle AD trial evaluating RO7126209 in prodromal or mild‐to‐moderate AD (NCT04639050), and allowed caregivers to provide input on the protocol and holistic support that could alleviate the burden of participation. Key insights/recommendations from caregivers were used to develop guidance on trial design and supporting materials. Result: Feedback suggested participants are motivated by being able to help others (including their families) avoid the suffering they experience, decreasing their sense of isolation, and access to state‐of‐the‐art care, testing, and neurology teams. Caregivers noted their participation goes far beyond study visits: they prepare participants for visits physically (e.g. washing, dressing) and mentally (e.g. detailing what visits will involve and supporting anxious or angry loved ones), accompany them on visits, and help participants recover from their change in schedule. Caregivers also carry the psychological burden of providing continual reassurance and being the sole person to answer participant's questions, particularly until trust is built with the study team, and face challenges in taking time off and re‐organizing appointments where necessary. Conclusion: Caregiver support and time commitments go far beyond study visits. The guidance provided by caregivers in the CareRing initiative has helped us adapt the design and holistic management of the Brainshuttle AD trial, and co‐create/refine specialized support for both caregivers and participants.